Management of Children with Atopic Dermatitis: A Narrative Review - Masoud Golpour; Javad Ghaffari; Abbas Dabbaghzadeh; Javad Rezaiefard (Mazandaran University of Medical Sciences, 2016)
Context Atopic dermatitis is a chronic, relapsing skin disorder that affects all ages including infancy and childhood. There are many proved and unproved treatments for atopic dermatitis. Evidence Acquisition Data sources of this narrative review included studies about pediatric atopic dermatitis with the following keywords, pediatric, atopic dermatitis, immunity, acute, chronic, pruritic inflammatory skin disorder, infancy, childhood, diagnosis, management and treatment. All of the articles were written in English language with full text on management or treatment. Results Innate and adaptive immune system involved atopic dermatitis. Major characteristics of atopic dermatitis include pruritus, chronic or relapsing lesions and personal or family history of atopic disease. There is no specific treatment for atopic dermatitis. The treatment included rehydration, emollients, topical steroid, calcineurin inhibitors and immunosuppressant. Crisaborole topical ointment, a PDE4 anti-inflammatory topical agent (phase three of the research) could be effective in atopic dermatitis. Conclusions Avoidance from trigger factors and emollients are basic treatments of atopic dermatitis.